(untitled) (Scientific journal of the Fergana State University, 2024)
The article will comment on the modus. Modus is derived from the Latin word "modius" meaning measure, type, rule. Modus was originally applied to the science of logic to represent forms of affirmation or negation of thought through speech. The science of Modus linguistics significantly expands the subject of research. That is, if purely linguistic issues are limited to semantic, syntactic analysis of the text, then the modus requires that the text contains a category of logic and enters into a scientific discussion precisely on the analysis of thought, which is implied in the logic of the text. The phenomenon of thought and modus, understood from the text, is inextricably linked with each other. For this reason, the modus was originally studied from the point of view of literary studies. Within the discipline of literary studies, modus connects with the expression of thought that receives the main emphasis, and it is more artistically evaluated. In the essence of Modus lies a critical attitude, analysis, assessment and subjective opinion. Within the science of linguistics, this concept is a relatively new term. In linguistics, this issue is studied as part of the direction of pragmalinguistics.